Pengaruh Product Quality dan Brand Experience terhadap Kepuasan Konsumen - Refani, Irsya Dwi; Adityarini, Esthi; Irawan, Anggi (Jurnal Informatika Ekonomi Bisnis, 2025)
This research was grounded in the decline in sales experienced by the Innisfree brand in recent times. Multiple variables affect this phenomenon, such as product quality and brand experience. Therefore, this research aimed to examine the influence of product quality and brand experience on Innisfree consumer satisfaction. A quantitative approach was employed by distributing questionnaires and using multiple linear regression analysis on 101 respondents. The outcomes indicated that product quality and brand experience jointly influence consumer satisfaction, with a contribution of 69.9%. It is evident that product quality and brand experience are important factors in increasing consumer satisfaction, thereby helping the company address its declining sales.